A expressão de futuridade na escrita jornalística manauara dos anos 80 aos dias atuais: um estudo sociofuncionalista - Araújo, Jussara Maria Oliveira de (2016)
The Brazilian Portuguese’s expression of futurity constitutes a variation phenomenon, and in several regions of Brazil and recently in the state of Amazonas it has been object of several research approaches: linguistic, sociolinguistic, functionalist and as a new theoretical trend, sociofunctionalist. When verifying these analysis, one notices a concurrence between the synthetic form of formulate the future (viajarei) and the periphrastic form (vou viajar) specially the construction composed by the verb ir (to go) + infinitive. The referred analysis had demonstrated the frequent occurrence of the innovative form (periphrasis) at the language’s oral modality. Oliveira (2012), Andrade (2012), Ribeiro (2012) and Barros (2015) confirm that the composed future is indeed advanced in the speech. However, at the present dissertation, was considered relevant verify how this phenomenon occurs in the writing, aiming to identify which contexts favor or don´t favor its execution. Therefore, the samples are originated from journalistic writing, and the expression of futurity used by three newspapers from the city of Manaus, Amazonas was examined: A Crítica, Diário do Amazonas and Dez Minutos. The first and second are older, having samples from the 80´s and 90’s, while the third one had its first edition in 2008. The newspaper´s choice was motivated by their representativeness among the papers read by Manaus’s society, considered its social segments. The present research uses the theoretical sociofunctionalist perspective. The linguistic factors analysis is primarily based in Oliveira (2012) and Almeida & Figueiredo (2014). The selected extralinguistic variables are: the social classes to what each newspaper is aimed: elite, middle class and popular, and the context variables, related to the different paper sections such as Politics, Economy, Sports etc. Data analysis was made by statistics software GoldVarbX, considering 13 variation factors. Results did show that although periphrasis is present at journalistic writing, it does not overcomes the use of the synthetic form. Keywords: Periphrasis; Writing; Variation.